Exploring Self-Confidence in English Skills and Informal Digital Learning Frequency: A Study of Indonesian Elementary Students - Syah, Neyla Rosa Istaufi; Suyitno, Imam; Anggraini, Ade Eka; Kusumaningrum, Shirly Rizki; Ekawati, Ratna (Journal of Language and Literature Studies, 2025)
This research explores the self-confidence of Indonesian elementary school students in their English skills and the frequency of their engagement with Informal Digital Learning of English (IDLE) activities, both receptive and productive. A quantitative survey design was employed, involving 103 Indonesian elementary school students who completed a 5-point Likert scale instrument measuring both receptive and productive IDLE activities, as well as students’ confidence in various English language tasks. The findings reveal that students engage more frequently in receptive IDLE activities—such as listening to English songs and watching subtitled English movies—than in productive ones like emailing or speaking via video calls. Despite this, overall participation in IDLE activities remains low. Furthermore, students exhibit higher self-confidence in receptive skills, particularly in understanding their teacher’s spoken English, while confidence declines significantly for productive tasks such as oral presentations or discussing past experiences. These patterns highlight a preference for passive exposure to English and suggest a need for more structured opportunities to engage students in active language use. These findings provide valuable contributions and insights into English language teaching and learning in early education, highlighting the recommendation for strategies, teacher training, and parental involvement that support EFL learners and educators in diversifying methods to learn English as a foreign language, ultimately promoting greater self-confidence and digital engagement among students.